Characterization of polymorphisms in the mannose-binding lectin gene promoter among human immunodeficiency virus 1 infected subjects - VALLINOTO, Antonio Carlos Rosário (2013)
The present study investigated the prevalence of mutations in the -550 (H/L) and -221 (X/Y) mannose-binding lectin (MBL) gene promoter regions and their impact on infection by human immunodeficiency virus 1 (HIV-1) in a population of 128 HIV-1 seropositive and 97 seronegative patients. The allele identification was performed through the sequence-specific primer polymerase chain reaction method, using primer sequences specific to each polymorphism. The evolution of the infection was evaluated through CD4+ T-lymphocyte counts and plasma viral load. The allele and haplotype frequencies among HIV-1-infected patients and seronegative healthy control patients did not show significant differences. CD4+ T-lymphocyte counts showed lower levels among seropositive patients carrying haplotypes LY, LX and HX, as compared to those carrying the HY haplotype. Mean plasma viral load was higher among seropositive patients with haplotypes LY, LX and HX than among those carrying the HY haplotype. When promoter and exon 1 mutations were matched, it was possible to identify a significantly higher viral load among HIV-1 infected individuals carrying haplotypes correlated to low serum levels of MBL. The current study shows that haplotypes related to medium and low MBL serum levels might directly influence the evolution of viral progression in patients. Therefore, it is suggested that the identification of haplotypes within the promoter region of the MBL gene among HIV-1 infected persons should be further evaluated as a prognostic tool for AIDS progression.